Implementasi Moderasi Beragama Pada Unit Kegiatan Mahasiswa Badan Dakwah Kampus Universitas Panca Marga - Hakim, Lukman (SETYAKI : Jurnal Studi Keagamaan Islam, 2023)
Probolinggo is one of the regions in Indonesia that boasts a diverse range of cultures, languages, ethnicities, and religions. This diversity can be a contributing factor to divisions and even conflicts. Religious moderation within the campus environment of Panca Marga University is a collective effort to enhance awareness and promote unity. The implementation of religious moderation within the Student Islamic Propagation Organization (BDK) aims to instill moderate values and tolerance in students as preparation for engaging within the broader society. This research employs a qualitative descriptive approach. This chosen approach enables researchers to attain a deeper comprehension from the perspective of the research subjects. This method places a particular focus on field observations, which are carried out to gather precise data by directly engaging with the research subjects. Data collection techniques involve interviews, documentation, and observations. The author utilizes a qualitative descriptive method with the aim of investigating the mentioned situations and conditions, with the outcomes being suitable for presentation in a research report. The findings of this study indicate that religious moderation activities within the Student Islamic Propagation Organization encompass various aspects, including scholarly, artistic, social, cultural, and religious activities.